Prenatal diagnosis of aneuploidies in amniotic fluid by multiple ligation-dependent probe amplification (MLPA) analysis - Hamidah, NH; Munirah, AR; Hafiza, A; Farisah, AR; Shuhaila, A; Norzilawati, MN; Jamil, MY; Ainoon, O (Malaysian Journal Pathology, 2024)
Prenatal diagnosis is essential in the new era of diagnosis and management of genetic diseases in obstetrics. Multiple ligation-dependent probe amplification (MLPA) is a recent technique for prenatal diagnosis for the relative quantification of 40 different nucleic acid sequences in one single reaction. We had utilized the MLPA technique in detecting aneuploidies in amniotic fluid samples from 25 pregnant women from the Obstetrics and Gynaecology Department UKMMC, versus the quantitative fluorescent polymerase chain reaction (QF-PCR) method. Conclusive results were obtained in 18 cases and all were concordant with that of the QF-PCR. All four cases of trisomies were correctly identified including one case with maternal cell contamination.